Posture, Musculoskeletal Activities, and Possible Musculoskeletal Discomfort Among Children Using Laptops or Tablet Computers for Educational Purposes: A Literature Review - Korhan, Orhan (Springer Netherlands, 2014)
Educational ergonomics focuses on the interaction between educational performance and educational design. By improving the design or pointing out the possible problems, educational ergonomics can be utilized to have positive impacts on the student performance and thus on education process. Laptops and tablet computers are becoming widely used by school children and beginning to be used effectively for educational purposes. As the latest generation of laptops and tablet computers are mobile and lightweight compared to conventional personal computers, they support student-centred interaction-based learning. However, these technologies have been introduced into schools with minimal adaptations to furniture or attention to ergonomics. There are increasing reports of an association between increased musculoskeletal (MSK) problems in children and use of such technologies. Although children are among the users of laptops and tablet computers both in their everyday lives and at schools, the literature investigating MSK activities and possible MSK discomfort regarding children using portable technologies is limited. This study reviews the literature to identify published studies that investigated posture, MSK activities, and possible MSK discomfort among children using mobile technologies (laptops or tablet computers) for educational purposes. An electronic search of the literature published in English between January 1994 and January 2014 was performed in several databases. The literature search terms were identified and combined to search the databases. The search results that the resources investigating MSK outcomes of laptop or tablet use of children are very scarce. This review points out the research gaps in this field, and identifying areas for future studies.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Science Education, Musculoskeletal (MSK) discomfort; Education, Mobile technologies, Children; Educational Technology, Educational ergonomics; WISE USE, EDUCATION, SCIENTIFIC DISCIPLINES